Dukungan Kader dan Ibu Balita Terhadap Kegiatan Pelayanan Posyandu Balita di Kelurahan Liliba Kota Kupang - Patricia Sunarti Agun; Keraf, M.K.P. Abdi Keraf; Enjelita M. Ndoen (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Posyandu is a form of Community-Based Health Efforts. Posyandu for toddlers is a priority posyandu for mothers and children, especially toddlers. Community support for Posyandu activities in the working area of the Oepoi Health Center, especially in the Liliba Subdistrict, seems to have decreased as seen from the failure to achieve the target number of children under five being weighed. In addition, the availability of infrastructure facilities at Posyandu is incomplete, such as a lack of tables and chairs, so it is hoped that the people of the Liliba Village will support government programs in public health services. The purpose of this study was to find out the forms of community support for toddler posyandu service activities in the Liliba Village, Kupang City. The type of research used is qualitative with a narrative approach. There were twenty-three informants consisting of the head of the Oepoi Health Center, health workers at Pustu Liliba, Cadre, Mother Toddler and Lurah Liliba. The results showed that the form of community support for toddler posyandu service activities was emotional, informational support such as providing information related to posyandu opening days through WhatsApp group media, home visits, instrumental such as labor, time, cost and assessment such as the community assessing toddler posyandu activities in Liliba Village. goes well. It can be concluded that the implementation of Posyandu Balita service activities in the Liliba Village is going well according to the flow so that the people of the Liliba Village continue to maintain active posyandu visits and the community always provides support.